Asymmetric Responses of Energy Consumption in Malaysia: Evidence from Nonlinear ARDL - Tang, Chung-Siong; Kogid, Mori (International Journal of Energy Economics and Policy, 2022)
Many studies have modelled the prices, growth, technology and financial effects on energy consumption in a linear fashion. However, structural changes may trigger asymmetric or nonlinear behaviour in time series analysis. In this paper, we examine the asymmetric influence of economic growth, energy prices, technological innovations and financial development on energy consumption in Malaysia over the period between 1970 and 2018 using a nonlinear ARDL (NARDL) model. The empirical results uncover the existence of asymmetric cointegration relationship between variables. A positive shock in income, energy prices and financial development leads to high energy consumption. Surprisingly, a fall in income does not lower the energy consumption. The results do not provide any evidence of technological effect on energy consumption. In addition, the energy consumption responds more elastically to negative shock than positive shock, which has implications for energy policy. The results also suggest that the short-run and long-run effects are asymmetrical. All variables are found to have asymmetric causal effect on energy consumption in the short-run.